Calculation and Influencing Factors of the Operating Efficiency of Chinese Airports under High-Quality Development - Meng Shang; Chunjie Jia; Hui Li; Yu Liu; Junwei Cao (Discrete Dynamics in Nature and Society)
Based on the cross-sectional data of 40 large-scale international airports in China in 2019, this paper introduced natural and social factors into the calculation of airport operating efficiency and constructed a BCC-SFA-BCC-Tobit 4-stage analysis framework. Combining with the connotation of the “green, smart, humane, and safe” airport high-quality development, the paper applied the Tobit model to quantitatively analyze the influencing factors of the operating efficiency of airports, and the research shows that (1) the overall operating efficiency of the study airports is 0.734; in terms of the region, the operating efficiency of airports located in southwest and northwest regions is greatly affected by natural factors, while the operating efficiency of airports located in North China is mostly affected by social factors. (2) Under the perspective of human-earth relationship, the impact of natural factors on the operating efficiency of airports is greater than that of social factors, wherein PM2.5 and relative humidity have negative impact, while the actual foreign capital utilization of the city and domestic and foreign tourists have positive impact. (3) The regression results of the Tobit model indicate that green, smart, and safe indicators can promote the high-quality development of airports, while the humane indicator restrains the high-quality development of airports.